31.7k views
5 votes
{5x−2y=43x−4y=−6 What is the answer

User Yasaricli
by
5.1k points

1 Answer

6 votes

Answer:

(2,3)

Explanation:

5x - 2y = 4 (1)

3x - 4y = -4 (2)

Multiply equation 1 by 2

10x - 4y = 8 Subtract 2 from the equation on this line

3x -4y = - 6

7x = 14 Divide by 7

x = 14/7

x = 2

5x - 2y = 4

5*2 - 2y = 4

10 - 2y = 4

-2y = 4-10

-2y = - 6

y = -6/-2

y = 3

I may not have read this correctly. Please put those 2 equations on separate lines.

User Stanislav Mamontov
by
5.1k points